Covid-19 Shockwaves Disrupted the Indonesian Capital Market: Gelombang Kejutan Covid-19 Mengganggu Pasar Modal Indonesia - Ardiansyah , Ricco; Nurasik, Nurasik (Indonesian Journal of Law and Economics Review, 2024)
This study examines the impact of the Covid-19 pandemic on the Indonesian capital market by analyzing abnormal returns and trading volume activity in the LQ45 index stock group from 2018 to 2020. Using secondary data and a purposive sampling method, the research employs Paired Sample t-Test for hypothesis testing. The results show significant differences in abnormal returns and trading volume activity before and during the pandemic, indicating a strong market reaction to Covid-19. These findings underscore the need for strategies to mitigate the effects of global disruptions on the market. Highlights: 1. Market Reaction: Significant changes in abnormal returns, trading volume during Covid-19. 2. Methodology: Uses secondary data, Paired Sample t-Test for analysis. 3. Focus: Examines LQ45 index stocks, daily prices, and volumes 2018-2020. Keywords: Event Study, Covid-19 Impact, Indonesian Capital Market, Abnormal Returns, Trading Volume